A relação da segregação urbana e desigualdades educacionais nos municípios de Maringá, Paiçandu e Sarandi - PR - Pereira, Ana Carolina Torrente (2013)
Through the union among the studies of Urban Sociology and Sociology of Education notes the possibility of developing a range of studies that provide new insights into the field of opportunities and educational inequalities. This paper accomplishes the combination of these elements and seeks to correlate aspects of the reality of the urban territory with school performance. Based in the municipalities of Maringa, Paiçandu and Sarandi - these are the area of conurbation of the Metropolitan of Region Maringa - was raised academic performance of state schools of elementary education on the last years (8th grade / year 9) and socioeconomic data arranged in the areas weighting to which these educational units are located. Through descriptive analysis and multivariate linear regression was established behavior relative to one another. Specifically these socioeconomic data constitute the income and educational level of the head extracted from the 2010 Census of the IBGE and the Socio-Occupational Typology 2010. School performance was measured from the note of Brazil Proof / Saeb extracted by INEP 2011.